ETIKA PELAYANAN PUBLIK DI KANTOR KECAMATAN TANETE RIAJA KABUPATEN BARRU - Halisa, Nur; Adys, Abdul Kadir; Riskasari, Riskasari (Universitas Muhammadiyah Makassar, 2022)
ABSTRACTThis study aimed to find out the ethics of public services at the Tanete Riaja District office, Barru Regency. This study used qualitative research. The number of informants as many as 11 people were determined by using purposive sampling. Data collection was Carried out using interview, observation and documentation techniques. The results showed that the aspect of equality of rights had run well, it did not discriminate and serves the community regardless of ethnicity, race, religion and politics, aspects of justice, related to justice all people were treated equally, provided explanations during the service process and served the community well, the Loyalty aspect, related to loyalty, all employees were very loyal to their agencies, especially those who were honorary, even though the salary was not really enough but they were still loyal even though they had worked for years, the accountability aspect, related to accountability, had not been fully implemented properly.Keywords: Ethics, Public Service.